CSF3R and CALR mutations in paediatric myeloid disorders and the association of CSF3R mutations with translocations, including t(8; 21). (9th April 2015) - Sano, Hitoshi; Ohki, Kentaro; Park, Myoung‐ja; Shiba, Norio; Hara, Yusuke; Sotomatsu, Manabu; Tomizawa, Daisuke; Taga, Takashi; Kiyokawa, Nobutaka; Tawa, Akio; Horibe, Keizo; Adachi, Souichi; et al.
Summary Mutations in the colony‐stimulating factor 3 receptor (CSF3R) and calreticulin (CALR) genes have been reported in a proportion of adults with myeloproliferative disease. However, little is known about CSF3R or CALR mutations in paediatric myeloid disorders. We analysed CSF3R exons 14 and 17, and CALR exon 9, using direct sequencing in samples of paediatric acute myeloid leukaemia (AML; n = 521), juvenile myelomonocytic leukaemia (JMML; n = 40), myelodysplastic syndrome (MDS; n = 20) and essential thrombocythaemia (ET; n = 21). CSF3R mutations were found in 10 (1·92%) of 521 patients with AML; two in exon 14 (both missense mutations resulting in p.T618I) and eight in exon 17 (three frameshift mutations: p.S715X, p.Q774R, and p.S783Q; and five novel missense mutations: p.Q754K, p.R769H, p.L777F, p.T781I, and S795R). All of the patients with mutations in CSF3R exon 17 had chromosomal translocations, including four with t(8;21). At the time of reporting, seven of these ten patients are alive; three have died, due to side effects of chemotherapy. No CSF3R mutations were found in cases of MDS, JMML or ET. The only mutation found in the CALR gene was a frameshift (p.L367 fs) in one ET patient. We discuss the potential impact of these findings for the leukaemogenesis and clinical features of paediatric myeloid disorders.